A quarter millenium of uses and misuses of the turtle name Testudo scabra: Identification of the type specimens of T. scabra Linnaeus 1758 (= Rhinoclemmys punctularia) and T. scripta Thunberg in Schoepff 1792 (= Trachemys scripta scripta) - Rhodin, Anders G. J.; Carr, John L. (Zootaxa, 2009)
The turtle name Testudo scabra Linnaeus 1758 has variously and confusingly been used in association with nine different currently recognized nominal species in four separate families in both suborders of turtles. The name has not been recognized as valid since the early 1800s and has recently been synonymized as a nomen dubium under primarily two species: Emys trijuga Schweigger 1812 (= Melanochelys trijuga) and Testudo punctularia Daudin 1801 (= Rhinoclemmys punctularia) (both Geoemydidae). Other earlier attributions of the name, T. scabra L. sensu Statius Müller 1774, Schneider 1783, Retzius in Schoepff 1792, Thunberg in Schoepff 1792, Say 1824, or Agassiz 1857, have variously been referred to seven other currently recognized nominal species: two species of Leguat’s tortoises (= both Testudo vosmaeri Suckow 1798 = Cylindraspis vosmaeri, and/or Testudo peltastes Duméril and Bibron 1835 = Cylindraspis peltastes) (Testudinidae), Perrault’s tortoise (= Testudo indica Schneider 1783 = Cylindraspis indica) (Testudinidae), Testudo europaea Schneider 1783 (= Testudo orbicularis L. 1758 = Emys orbicularis) (Emydidae), Testudo galeata Schoepff 1792 (= Testudo subrufa Lacépède 1788 = Pelomedusa subrufa) (Pelomedusidae), Testudo scripta Schoepff 1792 (= Trachemys scripta) (Emydidae), and Testudo insculpta LeConte 1830 (= Glyptemys insculpta) (Emydidae). The previously unidentified type specimens of both T. scabra L. 1758 and Testudo scripta Schoepff 1792 have been located in the Linnaean and Thunbergian collections in Uppsala, Sweden. The latter species was described by Schoepff both as Testudo scabra sensu Thunberg and Testudo scripta Thunberg. Based on our examination, the holotype of Testudo scabra Linnaeus 1758 is Rhinoclemmys punctularia. To promote nomenclatural stability, we designate Testudo scabra Linnaeus 1758 as a nomen oblitum and nomen rejectum synonymized under Testudo punctularia Daudin 1801, already a nomen protectum. The type specimen of Testudo scripta Schoepff 1792 has not previously been identified, but is also present in the collection and represents Trachemys scripta scripta. Based on the circumstances of the description, the proper authorship of the name should be given as Testudo scripta Thunberg in Schoepff 1792, rather than T. scripta Schoepff 1792, as currently done.